WASHINGTON VIEW: Listen to American opinions. (September 2014) - Ferguson, Maria
The annual PDK/Gallup Poll of the Public's Attitudes Toward the Public Schools is coming out. It always gives us an important view of what Americans are thinking about their schools and education in general. There are important issues covered in the poll and we would do well to consider what the public is saying about our schools and we in Washington and across the country make and consider policy and initiatives for our future.